(untitled) (Biological Sciences - PJSIR, 2022)
To assess the relationship between maternal and fetal mineraI homeostasis, serum, calcium, magnesium inorganic phosphorus total protein, albumin and alkaline phosphatase concentrations in cord serum from 30 preterm 30 term and 30 term low-birth-weight neonates were compared with the material serum. There was a significant, relationship between the two compartment. A strong positive correlation was observed between the mineral levels of term and pre term feto-metemal compartment. No correlation was present between the mineraI levels of term low birth weight group except magnesium. Results of paired t-test indicate significant differences among the mineraI levels of three pregnant groups.